Path Planning of Restaurant Service Robot Based on A-star Algorithms with Updated Weights - Yang, Ruijun; Cheng, Liang (Proceedings of the International Symposium on Computational Intelligence and Design, 2019)
Through the real-time gridded restaurant congestion map, aiming at the shortest weighted path, and based on the degree of channel congestion to change the weight of the restaurant channel in real-time, the A Star algorithm is improved to find the optimal restaurant service robot path, and the gridded map of a restaurant is used to verify the results. The results show that, compared with the traditional gridded map of a restaurant, the proposed algorithm is effective. A star algorithm with constant path weight and improved A star algorithm can effectively avoid crowded channels and improve the mobile efficiency of service robots. It has a certain practical application value in restaurant service robot system.